Micromanagement: conditions influencing antipathogen function of the skin microbiome in spotted salamanders, Ambystoma maculatum - Barnhart-McCarty, Kelly; LaBumbard, Brandon; Kearns, Patrick J.; Ahsan, Rakeyah; Whetstone, Ross; Bletz, Molly; AlKhalifa, Saleh E.; Poltronetti, Anthony; Tokash-Peters, Amanda; Gabor, Caitlin R.; Schliep, Klaus; Umile, Thomas P.; et al. (Frontiers in Amphibian and Reptile Science, 2024)
The emerging fungal pathogen Batrachochytrium salamandrivorans (Bsal) threatens the diversity of amphibians, particularly in North America where it is projected to invade. Amphibian skin defenses include a mucosal layer containing microorganisms that can potentially modulate host response to pathogens such as Bsal. In this study, we focused on the composition of the skin microbiome across life stages of spotted salamanders (Ambystoma maculatum). We also evaluated the stress hormone corticosterone and skin microbiome response to inoculations with Bsal and probiotics at both the larval and juvenile developmental stages, and the response to different environmental conditions. Results indicated that both bacterial and fungal communities found on the skin significantly differed in structure and diversity between life stages of A. maculatum. Exposure to three different probiotics (Bacillus thuringiensis, Chryseobacterium rhizoplanae, and Penicillium sp.) and Bsal evoked shifts in the microbiome of larvae and juveniles, and the metabolite profile of the larval mucosal layer of A. maculatum. Despite changes in the microbiome, all tested probiotics and Bsal were unable to persist on the skin. Larval bacterial microbiomes shifted in response to Bsal and B. thuringiensis with no significant impacts on antifungal function or bacteria richness, however fungi strongly responded to Bsal and B. thuringiensis application. This indicates that developmental shifts in the microbiome can be initiated by microbial applications such as B. thuringiensis, a widely used mosquito larvicide. Overall, experimental results indicate that life stage, growth and development, and environmental conditions appeared to be the main factors driving changes in the amphibian skin microbiome and potential anti-Batrachochytrium function.